Epidemiology and Prevalence of Soft Tissue Sarcomas - Aneela Faisal Memon, Fida Hussain, Zainab Nisar, Faiz Muhammad Khoso, Suresh Kumar, Faheem Ahmed Memon (Drugs and Cell Therapies in Hematology, 2022)
Sarcomas make up more than 20% of all solid malignant tumor’s malignancies in children and in adults, solid malignant tumors account for less than 1% of all tumors. Bone tumors are the most prevalent type of sarcoma, accounting for roughly 10% of all sarcomas. Soft tissue sarcomas account for the vast majority of diagnosed sarcomas. Sarcoma’s hazards are underappreciated. The existing literature on sarcoma etiology and epidemiology was examined. Environmental exposures, genetic predisposition, and a combination of the two are all factors that can lead to sarcoma development. Despite the fact that HHV8 is the causal virus, HIV-positive people are more likely to develop Kaposi’s sarcoma. Radiation from radiotherapy has been related to the development of secondary sarcomas in some cancer patients. According to a recent meta-analysis, children with a history of hernias are more likely to acquire Ewing’s sarcoma (adjusted OR 3.2, 95 percent CI 1.9, 5.7).Osteosarcoma growth has been linked to during pubertal growth spurts, bone formation occurs. Sarcomas have been linked to occupational characteristics such as job type, industry, and chemical exposures herbicides and chlorophenols, for example. Case-control research indicated a significant growth in the risk of Gardeners are more likely than farmers to have soft tissue sarcoma (adjusted OR 4.1, 95 percent CI 1.00, 14.00). Blacksmiths, toolmakers, and machine-tool users have an increased risk of bone cancer, according to a European study (adjusted odds ratio 2.14, 95 percent confidence interval 1.08, 4.26). Maternal and paternal traits such as occupation, age, smoking status, and health challenges faced during pregnancy have also been proposed as sarcoma risk factors, and future studies will need to look into them. We discovered significant connections with sarcoma risk in the few papers we looked at, but many of these findings will need to be verified in larger populations.In addition, the biological mechanisms are poorly understood that underpin each epidemiologic connection studied in the studies. Molecular epidemiology in the future research could help us better understand hereditary vs. environmental factors influences on carcinogenesis in this frequently-fatal malignancy in adults and children.